Improving Information on Over-looked Generalists: Occurrence and Mitochondrial DNA Diversity of Campbell’s (Cercopithecus campbelli) and Green Monkeys (Chlorocebus sabaeus) in Guinea–Bissau, West Africa - Colmonero-Costeira, Ivo (2025)
Non-threatened primates are often overlooked in conservation efforts despite their increasing vulnerability to local extirpation. Campbell’s (Cercopithecus campbelli) and green monkeys (Chlorocebus sabaeus) are sympatric medium-sized West African guenons (tribe Cercopithecini) whose intraspecific genetic diversity remains understudied in most of their distribution. Both species are ecological generalists and are globally considered non-threatened. In Guinea–Bissau, C. campbelli and Chl. sabaeus are considered the most abundant of the ten extant primate species and are the most frequently hunted for meat. Their populations are thought to be decreasing and but up-to-date data on their occurrence in the country hinders their conservation status assessment. We aimed to update occurrence data and estimate the country-wide mitochondrial (mtDNA) genetic diversity for both species in Guinea–Bissau. From 2008–2022, we conducted surveys in four mainland protected areas and on the islands of the Bijagós Archipelago. We identified C. campbelli populations outside their known distribution. We found high mtDNA diversity for both species on the mainland and lower diversity in insular populations. Our results show significant signals of geographically induced mtDNA differentiation, particularly in C. campbelli. In Chl. Sabaeus, we found divergent haplotypes at geographically close locations. We identified differentiated haplogroups with an estimated divergence time of 1.53 million years ago (Ma) in C. campbelli and 1.16 Ma in Chl. sabaeus, possibly linked to Pleistocene climatic fluctuations. Given the local presence of differentiated mtDNA haplogroups across these and other primate species, we suggest that Guinea–Bissau should be considered as an important region for primate conservation in West Africa.